Post-activation performance enhancement: Acute effected after activation in kayak sprint - Khamros, W.; Peepathum, P.; Senakham, T.; Sriramatr, S.; Phongsri, K. (Journal of Physical Education and Sport, 2023)
Preconditioning strategies before a competition are extremely important, especially in sports that use speed and power as key performance benefits. Kayak sprint is a sport that requires the necessary use of power and speed as the key performance aspects, which may benefit from the strategies in this work. This study aimed to compare the acute effects and differences in post-activation performance enhancement (PAPE) on physiological and performance in kayak paddle. Twelve men kayak paddle sub-elite participated in this research through arandomized crossover trial. All participants performed three different protocols consisting of the Resistance activation protocol (2x4x80%1RM x Bench press and Bench row), Maximum sprint paddle (2x20 sec x rest interval 2 min), and the control group followed by a 3-minute test. Maximum power, power average, stroke per minute, total distance, percentage of heart rate and blood lactate concentration each period were measured. For the main effect of MANOVA, it was found that only maximum power performance in resistance activation and maximum paddle method was higher than the control group; no difference was observed in other variables. There was an interaction effect (Intervention x Period) of blood lactate found, in which Resistance activation and aximum sprint paddle were higher than the control group after the intervention period. Before the 3-minute test period, the Maximum sprint paddle was different from the other group, and resistance activation was higher than the control group 6 minutes after the test. Blood lactate showed significance in all periods except after intervention and before the 3-minute test period in the resistance activation and the Maximum sprint paddle group. Activation by using the resistance or maximum speed paddle method could improve maximum power temporarily. Blood lactate increased after intervention, persisted after the intervention, and continued for several minutes. The application of this method should be taken into consideration regarding the fatigue that occurs and potentially affects other performance indicators.